OsCPD1 and OsCPD2 are functional brassinosteroid biosynthesis genes in rice. (December 2022) - Zhan, Huadong; Lu, Mingmin; Luo, Qin; Tan, Feng; Zhao, Ziwei; Liu, Mingqian; He, Yubing
Abstract: CONSTITUTIVE PHOTOMORPHOGENIC DWARF (CPD), member of the CYP90A family of cytochrome P450 (CYP450) monooxygenase, is an essential component of brassinosteroids (BRs) biosynthesis pathway. Compared with a single CPD/CYP90A1 in Arabidopsis thaliana, two highly homologous CPD genes, OsCPD1/CYP90A3 and OsCPD2/CYP90A4, are present in rice genome. There is still no genetic evidence so far about the requirement of OsCPD1 and OsCPD2 in rice BR biosynthesis. In this study, we reported the functional characterization of OsCPD genes using CRISPR/Cas9 gene editing technology. The overall growth and development of oscpd1 and oscpd2 single knock-out mutants was indistinguishable from the wild-type, whereas, the oscpd1 oscpd2 double mutant displayed multiple and obvious BR-related defects. Cytological analyses further indicated the defective cell elongation in oscpd1 oscpd2 double mutant. The oscpd double mutants had a lower endogenous BR level and could be restored by the application of the brassinolide (BL). Moreover, overexpression of OsCPD1 and OsCPD2 led to a typical BR enhanced phenotype, with enlarged leaf angle and increased grain size. Taken together, our results provide direct genetic evidence that OsCPD1 and OsCPD2 play essential and redundant roles in maintenance of plant architecture by modulating BR biosynthesis in rice. Highlights: Single and double mutants of OsCPD genes are constructed via CRISPR/Cas9 gene editing tool. Oscpd1 oscpd2 double mutants develop multiple and obvious brassinosteroid-related defects. Overexpression of OsCPD1 and OsCPD2 led to a typical brassinosteroid enhanced phenotype.